The assembly factor Reh1 is released from the ribosome during its initial round of translation - Sharmishtha Musalgaonkar; James N. Yelland; Ruta Chitale; Shilpa Rao; Hakan Ozadam; David W. Taylor; Can Cenik; Arlen W. Johnson (Nature Communications)
Abstract Assembly of functional ribosomal subunits and successfully delivering them to the translating pool is a prerequisite for protein synthesis and cell growth. In S. cerevisiae, the ribosome assembly factor Reh1 binds to pre-60S subunits at a late stage during their cytoplasmic maturation. Previous work shows that the C-terminus of Reh1 inserts into the polypeptide exit tunnel of the pre-60S subunit. Here, we show that Reh1-bound nascent 60S subunits associate with 40S subunits to form actively translating ribosomes. Using selective ribosome profiling, we found that Reh1-bound ribosomes populate open reading frames near start codons. Reh1-bound ribosomes are also strongly enriched for initiator tRNA, indicating they are associated with early elongation. Using cryo-electron microscopy to image Reh1-bound 80S ribosomes, we found they contain A site peptidyl tRNA, P site tRNA and eIF5A, indicating that Reh1 does not dissociate from 60S until translation elongation. We propose that Reh1 is displaced by the elongating peptide chain, making it the last assembly factor released from the nascent 60S subunit during its initial round of translation.